Effects of diets during growth and their repercussion on the quantitative and qualitative characteristics of carcass - Tirapicos Nunes J.; Paiva J.C.; Gomes C.; Freitas A.B.; Almeida J.A. (Tradition and innovation in Mediterranean pig production, 2000)
In this experiment the following productive parameters were assessed: ADG, CI and the evolution of the back fat in Alentejano (AL) and cross-breed (LW x Duroc) x AL pigs, using two different diets: balanced commercial feed (A) vs Triticale (T) with premix and lysine supplements. 48 pigs were used (I.W. of 31.3 kg), which were split into four groups of 12: (i) Alentejano, fed with Triticale; (ii) Alentejano fed with commercial feed; (iii) Cross-breed, fed with Triticale; and (iv) Cross-breed, fed with commercial feed. The animals were weighed every fortnight. The amount of feed intake was assessed with the same frequency in order to determine the CI. The back fat thickness as well as the depth of the longíssimus dorsi were measured monthly, using echography. The animals were slaughtered at plus minus 100 kg live weight and ten months in age. A significantly higher (P less than 0.01) ADG was observed in the cross-bred animals.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)